Identification and characterization of extracellular vesicles from red cells infected with Babesia divergens and Babesia microti - Beri, Divya; Rodriguez, Marilis; Singh, Manpreet; Liu, Yunfeng; Rasquinha, Giselle; An, Xiuli; Yazdanbakhsh, Karina; Lobo, Cheryl A. (Frontiers in Cellular and Infection Microbiology, 2022)
Babesiosis is a zoonosis and an important blood-borne human parasitic infection that has gained attention because of its growing infection rate in humans by transfer from animal reservoirs. Babesia represents a potential threat to the blood supply because asymptomatic infections in man are common, and blood from such donors can cause severe disease in certain recipients. Extracellular vesicles (EVs) are vesicles released by cells that contain a complex mixture of proteins, lipids, glycans, and genetic information that have been shown to play important roles in disease pathogenesis and susceptibility, as well as cell–cell communication and immune responses. In this article, we report on the identification and characterization of EVs released from red blood cells (RBCs) infected by two major human Babesia species—Babesia divergens from in vitro culture and those from an in vivo B. microti mouse infection. Using nanoparticle tracking analysis, we show that there is a range of vesicle sizes from 30 to 1,000 nm, emanating from the Babesia-infected RBC. The study of these EVs in the context of hemoparasite infection is complicated by the fact that both the parasite and the host RBC make and release vesicles into the extracellular environment. However, the EV frequency is 2- to 10-fold higher in Babesia-infected RBCs than uninfected RBCs, depending on levels of parasitemia. Using parasite-specific markers, we were able to show that ~50%–60% of all EVs contained parasite-specific markers on their surface and thus may represent the specific proportion of EVs released by infected RBCs within the EV population. Western blot analysis on purified EVs from both in vivo and in vitro infections revealed several parasite proteins that were targets of the host immune response. In addition, microRNA analysis showed that infected RBC EVs have different microRNA signature from uninfected RBC EVs, indicating a potential role as disease biomarkers. Finally, EVs were internalized by other RBCs in culture, implicating a potential role for these vesicles in cellular communication. Overall, our study points to the multiple functional implications of EVs in Babesia–host interactions and support the potential that EVs have as agents in disease pathogenesis.